2008
DOI: 10.1002/jcp.21683
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β‐mediated nuclear interaction between IRS‐1 and Rad51 inhibits homologous recombination directed DNA repair in medulloblastoma

Abstract: In medulloblastomas, which are highly malignant cerebellar tumors of the childhood genotoxic treatments such as cisplatin or γ-irradiation are frequently associated with DNA damage, which often associates with unfaithful DNA repair, selection of new adaptations and possibly tumor recurrences. Therefore, better understanding of molecular mechanisms which control DNA repair fidelity upon DNA damage is a critical task. Here we demonstrate for the first time that estrogen receptor beta (ERβ) can contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 41 publications
(71 reference statements)
5
43
0
1
Order By: Relevance
“…Indeed, results in Fig. 6A (lower panel) confirmed that only a small fraction of nuclear IRS-1 was detected in Daoy cells treated together with cisplatin and ICI182,780, which according to our previous observation is expected to increase the fraction of Rad51, which in the absence of nuclear IRS-1 can be recruited more effectively to the sites of DSBs, supporting HRR [9], [36]. The results in Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, results in Fig. 6A (lower panel) confirmed that only a small fraction of nuclear IRS-1 was detected in Daoy cells treated together with cisplatin and ICI182,780, which according to our previous observation is expected to increase the fraction of Rad51, which in the absence of nuclear IRS-1 can be recruited more effectively to the sites of DSBs, supporting HRR [9], [36]. The results in Fig.…”
Section: Resultssupporting
confidence: 82%
“…5), the cells treated with cisplatin in the presence of ICI182780 (Cis+ICI) show an increase in γH2AX nuclear foci (evaluated by γH2AX/DAPI co-localization), which may imply more effective recruitment of DNA repair proteins, including Rad51 [35]. Of note, we have previously reported that ICI182,780–mediated inhibition of ERβ prevented translocation of IRS-1 to the nucleus and the binding between IRS-1 and Rad51 after DNA damage [9]. Indeed, results in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In melanoma, the tumor suppressor gene MEN1 and ERα bind to the promoters of RAD51 and BRCA1, therein activating transcription [49]. Conversely, ERβ functions to place RAD51 into an inactive complex with insulin receptor substrate 1 (IRS1), thus diminishing HR function in medulloblastoma [50] Additionally, ERβ antagonism results in cisplatin resistance as a result of enhanced RAD51-associated DNA repair [51]. Although the opposite effects of ERα and ERβ demonstrate complexity, this is not without precedent as ERα has pro-proliferative capacity in BrCa, while ERβ is growth inhibitive in many cancer types [52, 53].…”
Section: Hormonal Regulation Of Dna Repairmentioning
confidence: 99%
“…A presença deste sítio pode explicar a translocação do IRS1 para o núcleo, após sua ativação pelo IGF1R induzida pelo IGF1 [91]. Além disso, a presença de IRS1 nuclear em células que expressam antígeno-T do vírus JCV humano, antígeno-T SV40, integrinas, receptor α de estrogênio (ERα) e receptor β de estrogênio (ERβ), indica que o mesmo pode ser translocado pela associação com outras proteínas equipadas com NLS [89,90,[92][93][94]. Adicionalmente, nossos resultados preliminares indicaram a presença de IRS1 no núcleo de células leucêmicas da linhagem linfoide (Jurkat) [95].…”
Section: Substrato 1 Do Receptor De Insulina (Irs1)unclassified